2020
DOI: 10.1038/s41386-020-00828-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of dopamine-dependent transcription and cocaine action by Gadd45b

Abstract: Exposure to drugs of abuse produces robust transcriptional and epigenetic reorganization within brain reward circuits that outlives the direct effects of the drug and may contribute to addiction. DNA methylation is a covalent epigenetic modification that is altered following stimulant exposure and is critical for behavioral and physiological adaptations to drugs of abuse. Although activity-related loss of DNA methylation requires the Gadd45 (Growth arrest and DNA-damage-inducible) gene family, very little is k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 83 publications
(164 reference statements)
1
22
0
Order By: Relevance
“…In line with this, we found that cocaine treatment altered Dnmt3a/b and Tet1, and increased 5-meC levels in mouse germ cells (65). Also, recent studies have shown that both DA via DRD1 and NE via b−ADRs induce alterations in DNA methylation patterns in the CNS (33,80). Moreover, we have recently reported a U-shaped DRD1-dependent key testicular mechanism mediating cocaine-triggered increase in silent chromatin mark H3K27me3, decrease in active promoter mark H3K4me3, and increase in H4K16ac mark involved in histone to protamine replacement (66).…”
Section: An Open Window For Catecholamine-induced Epigenetic Reprogra...supporting
confidence: 86%
“…In line with this, we found that cocaine treatment altered Dnmt3a/b and Tet1, and increased 5-meC levels in mouse germ cells (65). Also, recent studies have shown that both DA via DRD1 and NE via b−ADRs induce alterations in DNA methylation patterns in the CNS (33,80). Moreover, we have recently reported a U-shaped DRD1-dependent key testicular mechanism mediating cocaine-triggered increase in silent chromatin mark H3K27me3, decrease in active promoter mark H3K4me3, and increase in H4K16ac mark involved in histone to protamine replacement (66).…”
Section: An Open Window For Catecholamine-induced Epigenetic Reprogra...supporting
confidence: 86%
“…DNA methylation levels are known to be altered both in response to drugs of abuse (Massart et al, 2015 ), and in LID (Figge et al, 2016 ). D1R stimulation has specifically been shown to rapidly upregulate expression of the DNA demethylase Gadd45b both in primary cultures and in vivo (Savell et al, 2020 ; Zipperly et al, 2021 ). Knockdown of Gadd45b impairs D1R-dependent changes in DNA methylation, which appear to be required for receptor-driven transcriptional activation, as well as cocaine reward (Zipperly et al, 2021 ).…”
Section: Signal Transduction Via the D1rmentioning
confidence: 99%
“…D1R stimulation has specifically been shown to rapidly upregulate expression of the DNA demethylase Gadd45b both in primary cultures and in vivo (Savell et al, 2020 ; Zipperly et al, 2021 ). Knockdown of Gadd45b impairs D1R-dependent changes in DNA methylation, which appear to be required for receptor-driven transcriptional activation, as well as cocaine reward (Zipperly et al, 2021 ). Gadd45b is similarly upregulated in LID, but interestingly, knockout of Gadd45b worsens the development of dyskinesia and increases the expression of other D1R-regulated genes such as Fos and Fosb (Park et al, 2016 ), suggesting that the demethylase may play distinct roles in different striatal subregions, or depending on specific disease context.…”
Section: Signal Transduction Via the D1rmentioning
confidence: 99%
“…DNA methylation in the VTA has been shown to play a role in associative memory combining environmental cues with drug reward (Day et al, 2013). Although DNA methylation was initially perceived as a stable process that cannot be rapidly modulated, subsequent studies have demonstrated that this is not the case (Miller et al, 2010;Zipperly et al, 2021). In the brain, DNA undergoes rapid methylation and demethylation, which is necessary for memory formation and synaptic plasticity (Feng et al, 2010;Miller et al, 2010;Day et al, 2013).…”
Section: Function Of Epigenetic Mechanisms In Preventing Drug Relapsementioning
confidence: 99%